Ontologia del tra. Metamorfosi e incontro per un’antropologia fenomenologica (Itinera, 2021)
Metamorphosis seems problematic for our occidental point of view. Becoming in general is viewed as an error or exception by our classic standpoint. In fact, it is strongly against identity and law of non-contradiction: A is fundamentally something different from B and for A it is impossible to be at the same time B. We need to think A as what-becomes-B in order to make metamorphosis possible. Anyway, how can A become B? As a matter of fact, this very claim has been historically the most common critic opposed to becoming. Deleuze and Guattari in their monumental work had tried to offer an enormous contribution to a few related problems. Redefining the subject as an event described by movement and affect can exceed the metamorphosis’ aporia. This new principle of individuation provides a new look upon arisen questions primarily because affects and movements are constant coordinates that define how metamorphosis is experienced. The paper tries to show how the betweenness (Zwischenheit; Aida; Traità) in action in the encounter with people, human beings, things, animals, plants and minerals defines the logic field of metamorphosis. This is shown in dialogue with the ontological turn in anthropology that is particularly focused on this affective and lively dimension of encounter especially among Amazonian populations. Actually this is also what happens in our – occidental and classical but live – relation with things and objects, as long as we try to think a real conceptualisation of experience.
Keywords: Metamorphosis, Becoming, Ontological Turn, Betweenness.